Adsorption Isotherms And Kinetic Studies On The Removal Of Lead (II) Ions By Rubber Seed Coat - Nor Hisyam, Nur Fatini (Universiti Sains Malaysia, 2021)
Rubber seed coats (RSC) were treated with acid and base to investigate the removal of lead (II) ions by adsorption process. Among all biosorbents that were investigated, base treated rubber seed coats showed the highest removal percentage of lead (II) ions. The experimental data were fitted to Langmuir, Freundlich, Temkin, Dubinin-Radushkevich and Halsey isotherm models to further describe the biosorption process. Generally, from adsorption isotherm models, base treated RSC have the characteristics such as having monolayer coverage of adsorbate on biosorbent surface, adsorption process of indirect interaction between adsorbent with adsorbate and it exhibits physical adsorption process. Next, experimental data were fitted to pseudo-first-order, pseudo-second-order, intraparticle diffusion and Elovich model. RSC showed best fit in pseudo-second-order kinetic model. RSC showed that surface adsorption may be contributing to the rate controlling step in the biosorption of lead (II) ions on RSC and based on Elovich kinetic model, chemisorption may be the rate determining step at higher concentration of lead (II) ions.